PENGARUH CUSTOMER RELATIONSHIP MARKETING TERHADAP LOYALITAS PELANGGAN INTERNET SPEEDY PADA PT. TELEKOMUNIKASI INDONESIA KANDATEL PANDAAN. - Alim, Khusnul; Murtadlo.,ME., Dr.H.A. Kholid (HERITAGE, 2014)
This study take title Customer Relationship Marketing influence on customer loyalty internet Speedy (Speedy Survey on Internet subscribers PT. Telekomunikasi Indonesia Kandatel Pandaan), the title was taken due to build relationships of trust and commitment at least, need to win the competition while improving service quality and satisfaction customers, improving customer loyalty and repairs can be done in various ways and strategies, a concept that can be guided is Customer Relationship Marketing.Explanatory research is research with quantitative approach through survey method approach that aims to determine the effect of customer relationship marketing on customer loyalty in internet Speedy PT. Telekomunikasi Indonesia Kandatel Pandaan, to know about it, then used multiple regression analysis with f test and t test, the sample size of this study were 100 respondents who subscribe inhternet Speedy, while testing instrument using the program SPSS 15 for windows.The results showed that the confidence variable (X1), commitment (X2), quality of service (X3) and customer satisfaction (X4) together (Simultaneous) has a significant influence on customer loyalty internet Speedy variable (Y), and from test t shows that the commitment variable (X2) and quality of service (X3) has a significant impact on customer loyalty. While consumer confidence variable (X1) and customer satisfaction (X4) had no significant effect on customer loyalty internet Speedy (Y)